2013
DOI: 10.1177/0148607113513800
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Interruptions to Nutrition Support in Critically Ill Children in the Pediatric Intensive Care Unit

Abstract: Prolonged time to nutrition initiation and interruptions in delivery caused pediatric patients to spend a high proportion of admission without nutrition support, preventing most from meeting energy requirements. Further research addressing specific patient outcomes is required to define optimal initiation times and appropriate procedural-specific fasting times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 27 publications
4
51
1
5
Order By: Relevance
“…EN interruptions have been described in both pediatric and adult critically ill patients (6). A significant proportion of these interruptions may be avoidable (6,23). A variety of strategies have been used to avoid unintended EN interruptions in the intensive care unit, including the use of the postpyloric route, stepwise algorithms, and volume-based feeding (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…EN interruptions have been described in both pediatric and adult critically ill patients (6). A significant proportion of these interruptions may be avoidable (6,23). A variety of strategies have been used to avoid unintended EN interruptions in the intensive care unit, including the use of the postpyloric route, stepwise algorithms, and volume-based feeding (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Rogers et al reported that fluid restriction was a major factor limiting nutrient intake in pediatric cardiac patients 3 . Fasting prior to procedures, failure to reinstitute timely nutrient intake after procedures, and mechanical issues with feeding tubes have all been identified as other major contributing factors to EN interruptions 3,5,6,16 . These interruptions to EN may result in a nutrient deprivation for a high proportion of the illness course.…”
Section: Discussionmentioning
confidence: 99%
“…Early EN, though variably defined by investigators, promotes the achievement of energy and protein nutrition goals and is associated with improved survival in children in the PICU (9-12). In a multicenter retrospective study of 5105 critically ill children, 40% of them had EN delayed beyond 48 hours after admission to the PICU.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about obstacles to the initiation of EN although it is probable that they would be similar to those associated with the inability to achieve nutritional goals. Since many of the obstacles to achieving nutritional goals may be modifiable, it is possible that barriers to initiation of EN may be modifiable as well (12, 16, 18). The aim of this study was to determine the factors associated with delayed EN in critically ill children.…”
Section: Introductionmentioning
confidence: 99%